Conformation-Dependent QSPR Models: logP(OW) - Mühlbacher, Markus; El Kerdawy, Ahmed; Kramer, Christian; Hudson, Brian; Clark, Timothy (Journal of Chemical Information and Modeling, 2011)
Quantitative structure property relationships for predicting the water octanol partition coefficient, logP(OW), are reported. The models are based on local properties calculated at the standard isodensity surface using semiempirical molecular orbital theory and use descriptors obtained as the areas of the surface found in each bin in a predefined binning scheme. The effect of conformation is taken into account but was found to have little effect on the predictive power of the models. A detailed error analysis suggests that the accuracy of the models is limited by that of the experimental data and that the best possible performance is approximately +/- 0.5 log units. The models yield a local hydrophobicity function at the surface of the molecules.

Drug-induced phospholipidosis caused by combinations of common drugs in vitro - Glock, Mareike; Mühlbacher, Markus; Hurtig, Henoch; Tripal, Philipp; Kornhuber, Johannes (Toxicology in Vitro, 2016)
Drug-induced phospholipidosis (DIPLD), characterized by the accumulation of phospholipids within lysosomes, is suspected to impair lysosomal function and considered an adverse side effect of the administered medication. The increasing use of polypharmacy and the resultant elevated risks of adverse drug reactions raise the need to explore the effects of drug combinations with respect to their influence on side effects, such as DIPLD. In this study, we utilized an in vitro assay to investigate DIPLD that was caused by 24 commonly used drugs applied alone and in binary combinations with each other. Moreover, we attempted to predict the extent of DIPLD resulting from the combinations using a simple additive approach based on the increase in phospholipid levels caused by the single drugs. The results suggest that DIPLD, which was caused by combinations of drugs, occurs in an additive manner, depending on total drug concentration. Furthermore, we show that the extent of DIPLD can be predicted from the DIPLD caused by the single drugs. Thus, the simultaneous use of multiple drugs with PLD-inducing properties increases the event risk, as well as the severity of drug-induced phospholipidosis. The findings underline the importance of considering the DIPLD-inducing properties of drugs, especially in the context of polypharmacy.
EVALuna2:23782

Functional Inhibitors of Acid Sphingomyelinase (FIASMAs) - Kornhuber, Johannes; Tripal, Philipp; Gulbins, Erich; Mühlbacher, Markus (Sphingolipids: Basic Science and Drug Development, 2013)
Sphingolipids are not only structural components of biological membranes, but also play an important role in cellular signalling and, thus, are involved in cell proliferation and differentiation but also stress and cell death. It is therefore of great clinical relevance to define inhibitors of the enzymes involved in sphingolipid metabolism. Here, we describe the state of the art of functional inhibitors of the acid sphingomyelinase. The acid sphingomyelinase converts sphingomyelin to ceramide, a compound often involved in cell stress. We describe the structural and physicochemical properties, the distribution, the pharmacokinetics, the pharmocodynamics and the clinical use of direct and functional inhibitors of the acid sphingomyelinase.<br
Keywords: Acid sphingomyelinaseö; Functional inhibitors; Ceramide; Structure–property-activity relation